ANALISIS FUNGSI INTERMEDIASI LEMBAGA PEMBIAYAAN BANK PEMBIAYAAN RAKYAT SYARIAH (BPRS) AMANAH UMMAH DALAM MENGEMBANGKAN SEKTOR USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI BOGOR BARAT - Cholil , Ahmad; Sumengkar, Apung; Rahmat, Muhammad Imdadun (Institut Agama Islam Sahid Bogor, 2025)
Bank Pembiayaan Rakyat Syariah is a sharia bank that in its activities does not provide services in payment transactions. The legal form of BPRS is a limited liability company. BPRS may only be owned by Indonesian citizens and/or Indonesian legal entities, local governments, or partnerships between Indonesian citizens or Indonesian legal entities and local governments. The MSME sector has advantages and is very potential to be further developed through appropriate policies and support from appropriate institutions. The main problem faced by the MSME sector is in the form of capital. Data collection techniques are a method used by researchers to capture or collect qualitative information from interviews, documentation, research observations. The intermediary role of BPRS Amanah Ummah carried out by the bank does not yet exist, however, BPRS Amanah Ummah continues to help the community in order to meet their needs and provide subsidized housing to the poor and also distribute tabarru funds